Employee Performance: The Role Of Competence, Workload, And Discipline With Technology Utilization Moderation - Erisa Nazief; Betti Nuraini; Ronal Aprianto (UNIVED Press, 2025)
This study aims to determine the effect of Competence, Workload, and Employee Discipline on the Performance of Lubuk Linggau City Regional Secretariat Employees moderated by Technology Utilization. Employee performance is essential for government organizations in providing optimal service to the community. This research uses quantitative methods with multiple linear regression approaches and Moderated Regression Analysis (MRA). The research sample was 97 State Civil Apparatus at the Regional Secretariat of Lubuk Linggau City. The results showed that competence has a positive and significant effect on employee performance, workload has a negative and significant impact on employee performance, and discipline has a positive and significant effect on employee performance. Technology utilization significantly moderates the effect of competence on employee performance but weakens the impact of workload and discipline on employee performance. The implication is that organizations need to improve employee competence, manage workload, and enforce work discipline, as well as make optimal use of technology to improve employee performance